2000
DOI: 10.1007/s100720070077
|View full text |Cite
|
Sign up to set email alerts
|

Conventional external radiotherapy in the management of clivus chordomas with overt residual disease

Abstract: Cranial chordomas are uncommon tumors accounting for less than 1% of all intracranial neoplasms. Although they are slowly growing, rarely metastasizing tumors, cranial chordomas are challenging to treat due to their critical location, invasive nature and aggressive recurrence. The aim of this retrospective study was to evaluate the role of conventional irradiation in the treatment of clival chordomas with overt residual disease after incomplete surgery. Between January 1979 and December 1997, 18 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(43 citation statements)
references
References 12 publications
1
38
1
3
Order By: Relevance
“…Zorlu et al [25] reported that in the case of overt residual tumor, the 5-year survival rate was 35% with clival chordoma when 60 Gy of adjuvant conventional radiotherapy was given. But when maximum surgical cytoreduction was tried, the control rate of adjuvant radiotherapy was greatly improved.…”
Section: Tumor Responsementioning
confidence: 99%
“…Zorlu et al [25] reported that in the case of overt residual tumor, the 5-year survival rate was 35% with clival chordoma when 60 Gy of adjuvant conventional radiotherapy was given. But when maximum surgical cytoreduction was tried, the control rate of adjuvant radiotherapy was greatly improved.…”
Section: Tumor Responsementioning
confidence: 99%
“…Results are summarized in Table 3. [58][59][60][61][62][63][64][65][66][67][68] For these diseases, particle therapy has been historically employed, results in terms of local control and progression free survival with photons RT are acceptable for chondrosarcoma but were on average rather disappointing for chordomas with only one series reporting 5-year local control in excess of 80% and other series reporting local control or progression free survival from 15% to 66%. It is difficult to draw any conclusions from these scarce and heterogeneous data; nevertheless, outcome appears not to be equivalent to that of particles and these findings may suggest that even modern advanced photons cannot achieve adequate target coverage in the skull base for prescription doses in excess of 70 Gy.…”
Section: Clinical Results With Photon External Beam Radiotherapy (Ebrt)mentioning
confidence: 99%
“…The recommended dose was more than 65-70 Gy (25,26). Previously, we reported our treatment results of skull base chordomas treated with conventional radiotherapy (27). The five-year PFS and OS rates were found to be 23% and 35%, respectively.…”
Section: Discussionmentioning
confidence: 99%